Beginning game programming - Harbour, Jonathan S (Cengage Learning, 2015)
Includes index; "This completely updated fourth edition of the popular Beginning Game Programming will introduce you to the fascinating world of game programming for Windows using Visual Studio 2013 and DirectX. The book requires only a basic understanding of the C++ language and provides a solid introduction to DirectX programming. You'll learn the basics of making sprite-based games without getting bogged down in complex 3D rendering. The instruction is step-by-step, building as you go. Even if you're new to the subject, you will be able to follow along, learning how to take your game ideas from concept to reality using today's standard professional game-creation tools. At the end of the book, you will put your new skills to use creating your own complete, fully functional game. Get started in game programming today, with Beginning Game Programming, fourth edition." -- Unedited summary from book